Lessons Learned While Clerking - Darrell W. Clark (Washington University Journal of Law & Policy, 2017)
This Article explores some of the important lessons learned by a former law clerk of Judge Barry Schermer. Clark attributes many of the “soft skills” he learned in his legal career to Judge Schermer, and shares those with younger colleagues. The Author concludes Schermer’s advice on being practical, including delegating tasks and preparing for court, also taught him the professionalism he learned in his early days after law school.
Keywords: Washington University School of Law; Clerkship; Federal Clerkship; Bankruptcy; Judge Schermer